Chloroprocaine 10 mg/ml for low-dose spinal anaesthesia in perianal surgery: a randomised dose finding study - Gebhardt, Volker; Müller-Hansen, Lasse; Schwarz, Anke; Bussen, Dieter G.; Weiß, Christel; Schmittner, Marc (Acta anaesthesiologica Scandinavica, 2017)
Background Low-dose spinal anaesthesia is a safe and reliable anaesthesia technique in outpatient perianal surgery. Regarding its short duration of action and its trend to hyperbaric characteristics, plain chloroprocaine 10 mg/ml seems to be ideal to perform low-dose spinal anaesthesia. The aim of this trial was to determine the optimal dosage of chloroprocaine for this indication. Methods Hundred and twenty patients undergoing perianal surgery were enrolled and randomly allocated to receive 10, 20 or 30 mg of chloroprocaine 10 mg/ml intrathecally. Patients had to sit upright for at least 10 min after injection. We measured the expansion of sensory and motor block and the times until voiding, walking without assistance and home discharge. Results The expansion of the sensory (P ≤ 0.0059) and the motor block (P ≤ 0.0086) gained with increasing doses. At a dose of 30 mg the incidence of a profound, clinically relevant motor block was significantly higher compared to 10 and 20 mg (P ≤ 0.0004). In the 10 mg group two patients suffered from nociceptive pain due to an incomplete block and five patients announced discomfort during procedure. Doses of 10 and 20 mg led to a significantly earlier discharge compared to 30 mg (P = 0.0003; P = 0.0406). Conclusion Plain chloroprocaine 10 mg/ml can successfully be used for low-dose spinal anaesthesia in perianal outpatient surgery. Regarding the unfavourable motor block and later discharge-times in the 30 mg group on the one hand and the block-failures in the 10 mg group on the other, 20 mg can be recommended as the optimal dose.
First published: 28 November 2016
Gesehen am 25.04.2018